ISOLASI MINYAK ATSIRI BUNGA MELATI BELANDA (Combretum indicum) DENGAN METODE DESTILASI UAP AIR DAN PENGGUNAANNYA PADA SEDIAAN AROMATERAPI - Hawa, Siti; Jailani, Jailani; Turista, Dora Dayu Rahma; Purwati, Sri (BIOEDUKASI (Jurnal Pendidikan Biologi), 2025)
The Dutch jasmine plant (Combretum indicum) from the Combretaceae family is an aromatic ornamental plant known for its pleasant fragrance and vibrant flowers. This study aimed to formulate and evaluate aromatherapy preparations derived from Dutch jasmine essential oil and to determine the optimal formulation that meets physical quality standards for aromatherapy products. The research employed a true experimental design with quantitative and qualitative descriptive analyses. Four formulations were developed using different concentrations of essential oil: 2% (F1), 3% (F2), 4% (F3), and 5% (F4). The formulations were evaluated through hedonic testing by 35 panelists using a standardized assessment sheet. Data were analyzed using descriptive statistics with Microsoft Excel. The results showed that among the four formulations, the 4% essential oil formulation (F3) received the highest preference score from panelists and met the physical quality criteria for aromatherapy products. Therefore, the F3 formulation was identified as the most effective and desirable aromatherapy preparation derived from Dutch jasmine essential oil.